Analysis of the Causes of Multifilament Thread Defects in PT X Using Seven Tools - Nafis, Maulida Durrotun; Joumil Aidil Saifuddin Zuhri (Yayasan Kita Menulis, 2026)
PT X, a leading plastic packaging manufacturer in Indonesia, faces the problem of high defect rates in the production of multifilament yarns that hinder output optimization. This research aims to analyze and improve product quality using the Seven Tools method. Data for the May-October 2025 period shows a total production of 214,045.5 kg with an accumulated defect of 5,029 kg. The results of the Pareto analysis identified two main defects (vital few), namely brittle yarn (38%) and easily broken yarn (31%). Analysis via the control map (p-chart) showed the process was in an uncontrolled condition, especially in August which exceeded the upper control limit (UCL 0.0242). Based on the fishbone diagram, the root cause of the problem comes from the instability of the engine temperature (godet), operator negligence, non-standard SOP, and variations in material quality. To overcome this, it is recommended that companies carry out routine machine maintenance (PPM), install automatic temperature monitoring systems, standardize SOP, and hold periodic training for operators to create process stability and minimize defects on an ongoing basis.